Translating narrative space in childrenas fiction Bronze and Sunflower from Chinese to English - Zhao, Meijuan; Ang, Lay Hoon; Toh, Florence Haw Ching (SAGE Publications, 2022)
Translating narrative space is a necessity due to its fundamental role in children’s literature. To date, studies have shown that efforts to examine the strategy in rendering the space issues in children’s literature translation remain scarce. Responding to that, the paper aims to explore how narrative space is transferred from one language to another. The theoretical framework is based on Ryan et al.’s model of narrative space and Baker’s framing strategies. A qualitative approach is designed to study the renowned Chinese children’s literature Bronze and Sunflower and its English version. A total of 146 examples are purposively selected as the samples. The findings show that selective appropriation is the most frequently used framing strategy. Also, it is observed that the translator prefers to omit some repeated settings and descriptions of spatial frames even though the source text elaborates them, consequently softening the sense of space in the target context. The findings may provide new insights into a better understanding of spatial issues in the translation of children’s literature.